Pengaruh Model Pembelajaran Stimulation, Investigation, Review, And Inference (SIRI) Terhadap Berpikir Kreatif Peserta Didik pada Materi Sistem Eksresi Kelas XI di SMAN 21 Gowa - Yaqin, Ainul; Hamansah, Hamansah; Zulkarnaim, Zulkarnaim; Syahriani, Syahriani; Hasanah, Ummul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the Stimulation, Investigation, Review, and Inference (SIRI) learning model on students creative thinking skills in the excretory system topic for Grade XI students at SMAN 21 Gowa. The research employed a quasi-experimental method with a nonequivalent control group design. The research population consisted of 104 grade XI students, with a sample of 70 students selected purposively. The data collection method used non-tests (observation) and tests. The data were analyzed descriptively and quantitatively. The average creative thinking skills score of students in the experimental class was 79.5, while in the control class it was 76.42. The analysis revealed a significant difference between the learning outcomes of students taught using the SIRI learning model and those taught without it (Sig. < α = 0.001). Based on these findings, it can be concluded that the SIRI learning model is effective in improving creative thinking skills students in the excretory system topic.